Apheresis technology correlates with bacterial contamination of platelets and reported septic transfusion reactions. Issue 12 (6th September 2017) - Eder, Anne F.; Dy, Beth A.; DeMerse, Barbara; Wagner, Stephen J.; Stramer, Susan L.; O'Neill, E. Mary; Herron, Ross M.
Abstract : BACKGROUND: Apheresis technology to collect platelet (PLT) components differs among devices. We evaluated the relationship of the plateletpheresis device with bacterial contamination and reported septic transfusion reactions. STUDY DESIGN AND METHODS: Plateletpheresis was performed using Amicus (Fenwal, a Fresenius Kabi Company) or Trima (Trima Accel, TerumoBCT) from 2010 to 2014. All donations used inlet‐line sample diversion and were tested by quality control (QC; Day 1) aerobic culture. Rates of bacterial contamination and septic reactions to PLTs were calculated for both devices. RESULTS: During the 5‐year study period, plateletpheresis collections using Amicus and Trima devices totaled 1, 486, 888 and 671, 955 donations, respectively. The rate of confirmed‐positive bacterial cultures of apheresis PLT donations was significantly higher with Amicus than with Trima (252 vs. 112 per 10 6 donations [odds ratio OR, 2.3; 95% confidence interval CI, 1.8‐2.9]). Septic transfusion reactions were caused by 30 apheresis PLT units from 25 contaminated Amicus procedures and three apheresis PLT units from three contaminated Trima procedures. The overall rate of septic reactions was significantly higher with apheresis PLT components collected with Amicus than with Trima (16.8 vs. 4.5 per 10 6 donations [OR, 3.8; 95% CI, 1.1‐12.5]). All apheresis PLT components implicated in septic transfusion reactions had negative QC culture results incubated through Day 5 (i.e., false negatives). CONCLUSION: Apheresis technology affects bacterial contamination of plateletpheresis collections. The device‐specific, higher rate of confirmed‐positive bacterial culture results also correlated with a significantly higher rate of reported septic transfusion reactions to apheresis PLTs.